The benefits of extrinsic ligament release for potentially hemodynamically unstable pancreaticoduodenal arcade aneurysm with median arcuate ligament syndrome: a case report - Terayama, Takero (BMC Surg, 2019)
BACKGROUND: A pancreaticoduodenal artery aneurysm (PDAA) occurring in close association with median arcuate ligament syndrome (MALS) is rare. A surgical procedure, such as median arcuate ligament (MAL) release, should be considered in such cases, but the operative criteria remain unknown. In this study, we reported an extremely rare case of PDAA with periarteritis nodosa (PAN) and MALS. CASE PRESENTATION: A 60-year-old man was transferred to our department with sudden onset of abdominal pain. We initially diagnosed his condition as a PDAA rupture with MALS based on enhanced computed tomography (CT). We promptly performed transcatheter arterial embolization (TAE) of PDAA, and the angiogram showed stagnant contrast agent in the celiac trunk, indicating total celiac artery occlusion. Follow-up enhanced CT three weeks after the first TAE clearly demonstrated newly formed, multiple aneurysms in the pancreaticoduodenal arcade and the hepatic artery. These findings indicated a systemic disorder, such as PAN or segmental arterial mediolysis, as the underlying cause. Therefore, we started corticosteroid therapy and performed diagnostic angiography to clarify the celiac artery’s patency. Contrary to the initial angiography, the second angiography showed sustained blood flow in the celiac artery. Nevertheless, we performed both extrinsic MAL release and consecutive TAE because of the risk of multiple aneurysms rupturing due to an uncontrolled systemic disorder and consequent hepatic ischemia. The patient had no episode of recurrence until one year of follow-up. CONCLUSIONS: It is important to evaluate risk for hemodynamically unstable events to decide the best treatment strategy for MALS.